Tinjauan Sistematis Aktivitas Antioksidan Kombucha Bunga Telang (Clitoria ternatea L.) Berdasarkan Perbedaan Konsentrasi/Metode Fermentasi - Frya RahmanDanny; Fitri Nurul Aini; Oktarini Ramadhani Putri; Muhammad Fathin Juanda; Annisa Nurhatini; Regina Febiola; Dwintha Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
Systematic Literature Review (SLR) aimed at comprehensively analyzing the antioxidant activity and phytochemical profile of Kombucha , focusing primarily on the impact of substrate variations and fermentation time. Kombucha is recognized as a significant functional fermented beverage, possessing broad health benefits, including antioxidant, antibacterial, and hepatoprotective properties. These biological activities are highly influenced by the bioactive compounds produced during the fermentation process by the SCOBY (Symbiotic Culture of Bacteria and Yeast), such as polyphenols and flavonoids. The SLR method was chosen for its structured, objective, and comprehensive approach in identifying, evaluating, and synthesizing relevant research evidence. Literature searches were conducted across five academic databases: ScienceDirect, PubMed, Google Scholar, DOAJ, and GARUDA Portal , utilizing structured keywords to gather quantitative data on Phenolic/Flavonoid Content and IC₅₀/DPPH Inhibition values , as well as in vivo evidence concerning its hepatoprotective effects (SGOT/SGPT and Liver Histology). The data analysis seeks to identify bioactive trends , evaluate Kombucha’s effectiveness as a hepatoprotective agent , and pinpoint research gaps , ultimately generating an integrated scientific synthesis to support the development of high-value functional Kombucha products.